Solvent‐Dependent Asymmetric Synthesis of Alkynyl and Monofluoroalkenyl Isoindolinones by CpRhIII‐Catalyzed C−H Activation. Issue 15 (7th March 2018) - Li, Teng; Zhou, Chao; Yan, Xiaoqiang; Wang, Jun
Abstract: The asymmetric synthesis of alkynyl and monofluoroalkenyl isoindolinones from N‐methoxy benzamides and α, α‐difluoromethylene alkynes is enabled by C−H activation with a chiral CpRh III catalyst. Remarkably, product formation is solvent‐dependent; alkynyl isoindolinones are afforded in MeOH (up to 86 % yield, 99.6 % ee ) whereas monofluoroalkenyl isoindolinones are generated in i PrCN (up to 98:2 Z / E, 93 % yield, 86 % ee ). Mechanistic studies revealed chiral allene and E ‐configured alkenyl rhodium species as reaction intermediates. The latter is transformed into the corresponding Z ‐configured monofluoroalkene upon protonation in the i PrCN system and into an alkyne by an unusual anti β‐F elimination in the MeOH system. Notably, kinetic resolution processes occur in this reaction. Despite the moderate enantiocontrol for the formation of the chiral allene, the Z ‐monofluoroalkenyl isoindolinones and alkynyl isoindolinones were obtained in good enantiopurities by one or two sequential kinetic resolution processes. Abstract : A matter of solvent : Alkynyl and monofluoroalkenyl isoindolinones were generated with good enantioselectivities from N ‐methoxy benzamides and α, α‐difluoromethylene alkynes by C−H activation with a chiral CpRh III catalyst. Remarkably, the product formation is solvent‐dependent; whereas alkynyl isoindolinones are formed in methanol, monofluoroalkenyl isoindolinones are generated in isobutyronitrile.